SIMILARITIES AND DIFFERENCES OF MOOD IN ENGLISH AND UZBEK LANGUAGES - Norboyeva Mohinur, Mukhamadiyev Aziz Shavkatovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This comparative analysis looks at how mood is expressed differently and similarly in Uzbek and English. Grammatical moods, which include indicative, imperative, and subjunctive moods, are employed in both languages to express attitudes toward the states and activities that verbs describe. Different moods in English are categorized as follows: the indicative mood is used for factual statements, the imperative mood is used for demands, and the subjunctive mood is used for hypothetical or unreal circumstances. While having similar core moods, Uzbek has a more complex system with extra moods like the optative, which communicates wishes or desires, and the conditional, which is marked more clearly and conspicuously than in English. In addition, Uzbek's usage and development of moods are frequently impacted by agglutinative suffixes, in contrast to English's more rigid syntactic framework. It highlights a universal feature of human language while reflecting different linguistic and cultural settings because both languages use mood to achieve identical communicating tasks, despite these variations.